Use of Educational Facilities and Quality of Teaching in Selected Primary Schools in Buhweju District - Tukundane, Eugene; Balimuttajjo, Sudi; Tutegyereize, Jean (East African Journal of Education Studies, 2022)
The study assessed the relationship between the use of educational facilities and the quality of teaching in primary schools in the Buhweju District. It was guided by the following objectives; to establish the availability of educational facilities in primary schools, to find out the level of use of educational facilities, to examine the quality of teaching in primary schools and to assess the relationship between the use of educational facilities and the quality of teaching. The study was carried out using a cross-sectional survey design. The targeted population for this study included head teachers, chairmen, School Management Committee, and teachers. The study involved both qualitative and quantitative approaches. The study findings showed that the level of use of educational facilities was good (agree), with an overall mean score of 3.76. The study findings revealed that the quality of teaching was good (often) with a (mean score of 3.77). The study findings showed that there is a statistically significant relationship between the use of educational facilities and the quality of teaching r = 0.177 at P value = 0.019 < 0.05. It was concluded that the level of use of educational facilities in selected primary schools in the Buhweju District was good. It was also concluded that the quality of teaching in selected primary schools in the Buhweju District was good. It was further concluded that there was a statistically significant relationship between the use of educational facilities and the quality of teaching. Therefore, the effectiveness of the use of educational facilities influences the quality of teaching positively. It was recommended that the school administrators should make sure that there is an adequate good structure in classroom buildings. Headteachers should ensure the effective use of educational facilities to increase the quality of teaching in selected primary schools in the Buhweju District